Determination of Schottky barrier height and enhanced photoelectron generation in novel plasmonic immobilized multisegmented (Au/TiO2) nanorod arrays (NRAs) suitable for solar energy conversion applications. Issue 40 (24th August 2017) - Arshad, Muhammad Shahid; Trafela, Špela; Rožman, Kristina Žužek; Kovač, Janez; Djinović, Petar; Pintar, Albin
Abstract : We have determined the Schottky barrier height (0.23 eV) and efficient photoelectron generation in novel multisegmented Au/TiO2 nanorod arrays. Abstract : For the past several years, different strategies have been developed to design and fabricate Au/TiO2 nanostructures for solar-light-driven applications. Owing to the localized surface plasmon resonance properties of Au, Au/TiO2 nanostructures display extraordinary features including enhanced visible light harvesting, hot electron injection, and Schottky barriers to minimize back electron transfer; these factors maximize device performance. In this report, novel free-standing immobilized TiO2 and multisegmented Au/TiO2 nanorod arrays (NRAs) were successfully fabricated with a template-assisted electrodeposition technique to examine several physical phenomena like the Schottky barrier height (SBH), photoelectron generation, as well as the mechanism of hot electron transfer. Pristine TiO2 NRAs exhibit amorphous behaviour with strong absorption under UV-light; however, for Au/TiO2 NRAs, transverse and longitudinal plasmon modes were observed under visible light, which correlates closely with our theoretical predictions. The reduced binding energy of Au 4f7/2 and concurrent increase in the Ti 3+ –O species observed with X-ray photoelectron spectroscopy (XPS) is direct evidence for charge transfer from oxygen vacancies in TiO2 to Au segments. XPS analysis on valence band maxima (VBM) helps us to determine an SBH of 0.23 eV at the interface between the Au and TiO2 segments. The low value of SBH is attributed to the high density of oxygen vacancies in TiO2 due to the amorphous structure, and is very close to the theoretical literature value. Photoelectrochemical (PEC) measurements showed 4× improved photoelectron generation in Au/TiO2 NRAs in comparison to pristine TiO2 NRAs. This improvement is attributed to the hot electron injection, plasmonic resonance energy transfer (PRET) and efficient charge separation and migration due to the small SBH at the interface of Au and TiO2 . Our results concluded that novel immobilized multisegmented (Au/TiO2 ) NRAs have great potential for solar-light-driven applications.